Hammerhead ribozyme specifically inhibits vascular endothelial growth factor gene expression in a human hepatocellular carcinoma cell line. - Morino, F; Tokunaga, T; Tsuchida, T; Handa, A; Nagata, J; Tomii, Y; Kijima, H; Yamazaki, H; Watanabe, N; Matsuzaki, S; Ueyama, Y; Nakamura, M (2000)
Hammerhead-type ribozymes are often utilized to suppress the expression of target genes. We evaluated the efficacy of an anti-vascular endothelial growth factor (VEGF) hammerhead-type ribozyme against GUC at exon 1 of the VEGF gene in a cell-free system (in vitro) as well as in the hepatocellular carcinoma cell line HLF (in vivo). The anti-VEGF ribozyme (alphaVRz) specifically cleaved synthetic VEGF RNA substrate, but not other triplet sequences of VEGF RNA substrate in vitro. When the alphaVRz was introduced into HLF cells, the ribozyme suppressed not only VEGF mRNA level but also that of VEGF protein. These results suggest that this ribozyme selectively inhibits VEGF gene expression in human hepatocellular carcinoma cells.